Export Diversification Effects of Aid for Trade in sub-Saharan Africa - Stein Masunda (Atlantis Press, 2023)
This paper uses panel data of 42 sub-Saharan Africa countries from 2005 to 2015 to examine the effect of aid for trade (AfT) on export diversification. The average Hirschman-Herfindahl index measure of 0.77 indicates that the export basket of sub-Saharan African countries is very narrow. This is further supported by the low number of active products lines, about 100 products on average measured at the Standard International Trade Classification (SITC) 3-digit level. Empirical results indicate that export diversification in sub-Saharan Africa is enhanced by particularly Af T that is directed toward improving productive capacity.